Tamoxifen in breast conservation therapy. - Lee, K; Plowman, P; Gilmore, O; Gray, R (1995)
Breast conservation surgery for early breast cancer requires post-operative radiotherapy to give local control rates equivalent to mastectomy. Three hundred and thirty-five women presenting with symptomatic breast lumps and receiving radiotherapy and adjuvant systemic therapy at St. Bartholomew's, have actuarial 8-year local relapse-free rates of 90% for T1 and 83% for T2,3 presenting cases. Amongst 49 elderly and/or medically frail patients treated with a similar surgical policy but post-operative tamoxifen only (for standard risk features), the local relapse-free rates were 96% for T1 and 43% for T2,3. Most relapses occurred in the first 2 years in both groups. We conclude that, in the absence of high risk features (defined), breast conservation surgery and tamoxifen only is a safe option for T1 disease in the elderly, but that the risk of local relapse is considerably higher when this policy is employed for patients presenting with larger tumors.